Effects of internal, external and preference of attentional focus feedback instructions on learning soccer "Head Kick" - Micoogullari, B. O.; Kirazci, S.; Altunsöz, Ö. S. (Montenegrin Journal of Sports Science and Medicine, 2012)
The aim of this study was to investigate the effects of different types of feedback on learning soccer "head kick" of female adolescent. Novices performed head kick during two practice days [one week apart) for two weeks using either internal or external preference attentional focusing instructions. There was also a preference group who choosen their feedback type themselves. Internal focus feedback related with body movements, whereas external focus feedback related with movement effects. The subjects (N=64) were randomly assigned to three groups internal focus feedback group (IFF) (N=15), external focus feedback group (EFF) (N=15) and preference group (PF) (N=34). To promote learning two skill acquisition days for two weeks and one retention day was applied at initial day of third week. Technique of the skill was measured in acquisition days and targeting was measured in retention day. In technique measuring part, EFF group was significantly more accurate than IFF group, PF group was better than those two groups (PF>EFF>IFF). Similar to acquisition phase, EFF group was significantly more successfull than IFF group, PF group was better than those two groups (PF>EFF>IFF )in retention phase. Acquisition and retention phase results indicated significance main effect for attentional focus feedback groups. This study results` indicated that external focus feedback was more effective than internal focus feedback in terms of acquisition and retention of learning soccer head kick for students with limited amount of knowledge about this skill. This study also indicated that not only the source of attention but also control over to source of attention of preference was an important factor in the amount of retention.